2015
DOI: 10.3201/eid2111.150764
|View full text |Cite
|
Sign up to set email alerts
|

Association of Higher MERS-CoV Virus Load with Severe Disease and Death, Saudi Arabia, 2014

Abstract: More data are needed to determine whether modulation of virus load by therapeutic agents affects clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
75
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 23 publications
11
75
1
2
Order By: Relevance
“…Previous studies have shown that the severities of the illnesses caused by avian influenza are linked to host factors, including chronic diseases, immuno-suppressive disorders, delayed confirmation of infection and late antiviral treatment [5,24,25,26,27], as well as virus factors such as pathogenicity, replications and mutations [25,28]. In the present study, we aimed to identify the high risks associated with host factors with regard to fatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the severities of the illnesses caused by avian influenza are linked to host factors, including chronic diseases, immuno-suppressive disorders, delayed confirmation of infection and late antiviral treatment [5,24,25,26,27], as well as virus factors such as pathogenicity, replications and mutations [25,28]. In the present study, we aimed to identify the high risks associated with host factors with regard to fatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…22 In Korea, 36 (19.9%) of 181 confirmed MERS-CoV cases were HCWs. 27 Systematic thorough screening for MERS-CoV among contacts is needed for effective infection control of outbreaks. Comparing MERS-CoV with severe acute respiratory syndrome (SARS), most HCWs with SARS had symptomatic infection with an associated high case fatality rate.…”
Section: Discussionmentioning
confidence: 99%
“…These factors were related with severe disease and poor prognosis of MERS in previous reports. 1,12,13,15,16,34,35 Our study has several strengths and limitations. Due to its retrospective nature, there may be a bias regarding collecting medical information in retrospective manner.…”
Section: Discussionmentioning
confidence: 99%